STUDI KEPERILAKUAN KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK DAERAH - Pramita Sukma Wardani; Imam Subekti; Rosidi - (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2018)
Abstract, The Objective of this research study is to examine the effect of attitude toward tax compliance on compliance pay local tax through the inttention to comply and to examine the effect of trust over government on compliance pay local tax through perception of justice. Data collected from questionnaire and analyzed with PLS-based SEM techniques with software SmartPLS version 2.0. The result of the analysis show both attitude toward tax compliance were found to be significantly on compliance pay local tax through the inttention to comply and the effect of trust over government also have a significant effect on compliance pay local tax through perception of justice.